Role of prophylactic antibiotics in elective surgeries and postoperative surgical infections - Asif Ali, S.; Ehtesham Afzal, Md. (International Surgery Journal, 2020)
Background: Health care associated infections (HAIs) present a significant source of preventable morbidity and mortality. More than 30% of all HAIS are represented by surgical site infections (SSIs) making them most common sub types between 1.9% and 2.7% of all surgical patients. Joseph Lister “the man who made surgery safe” introduced antiseptic method for safe surgeries. As many are now considering antibiotics “wonder drug” which covers the surgical techniques and having asepsis. Extensive indiscriminate use of antibiotics has resulted in developing resistance. Methods: Study conducted in about 100 cases in various surgical units having various surgical procedures. Only clean cases are taken. A single stat dose of first generation cephalosporin 1gm given IV at the time of giving anesthesia. Postoperative any signs and symptoms like infections, fever with chills, wound discharge are observed. If any evidence of wound infection is present, accordingly sent for culture and sensitivity and suitable antibiotics are given. Results: In our study 5 patients had fever with serous discharge 2 patients showed no growth, 3 patients had got growth positive (2- staphylococcus aurous, 1- pseudomonas). Hence our infection rate is 3%. Conclusions: Single dose prophylaxis has got definite advantage to overcome the postoperative wound sepsis. Prolonged antibiotic therapy should be avoided as it has got no added advantages over single dose antibiotic.